PRINSIP MENCEGAH KERUSAKAN SEBAGAI LANDASAN PEMIKIRAN HUKUM EKONOMI SYARIAH - Yahya, Mohammad Hisyam; Na’im, Fairuz ‘Ainun (MASILE, 2023)
AbstractThis study aims to analyze the jurisprudential rule of preventing damage as a basis for sharia economic law thinking. This study uses qualitative methodology with a doctrinal research approach to Islamic law by conducting textual research, examining texts on fiqh rules from the Quran and Hadith. The results of the discussion is that this research concludes thatthe principle of preventing damage. The application of the principle ofpreventing damage in sharia economic law plays an important role in givingbirth to sharia economic principles and systems. The inclusion of the principle of preventing damage in the prohibition of usury, gharar, and maisir leads humanity to achieve one of the maqashid sharia, namely hifdh al-mal from wasting wealth and doing something that is hated by Allah, such as obtaining wealth by means of who is false, obtains something byspeculation, and relies on uncertainty.Keywords: prevent; damage; dangerous; sharia; economic; law